Atypical Intracranial Epidermoid Cysts: Rare Anomalies with Unique Radiological Features - Eric K. C. Law; Ryan K. L. Lee; Alex W. H. Ng; Deyond Y. W. Siu; Ho-Keung Ng (Case Reports in Radiology)
Epidermoid cysts are benign slow growing extra-axial tumours that insinuate between brain structures, while their occurrences in intra-axial or intradiploic locations are exceptionally rare. We present the clinical, imaging, and pathological findings in two patients with atypical epidermoid cysts. CT and MRI findings for the first case revealed an intraparenchymal epidermoid cyst that demonstrated no restricted diffusion. The second case demonstrated an aggressive epidermoid cyst that invaded into the intradiploic spaces, transverse sinus, and the calvarium. The timing of ectodermal tissue sequestration during fetal development may account for the occurrence of atypical epidermoid cysts.